The role of cardiac rehabilitation in heart failure: A review from an evidence-based approach - Irmansyah, Yos Akbar; Widi, Vina Sari Nugrahaning; Martiana, Astri Kurniati (Heart Science Journal, 2026)
Heart failure (HF) is a complex global health challenge caused by a structural and/or functional cardiac abnormality. Pharmacological medication remains a cornerstone of its management, but most patients continue to experience limited exercise capacity, which leads to decreased quality of life. Those limitations have led to the emergence of cardiac rehabilitation (CR) as a crucial part of HF management. It is a non-pharmacological, multidisciplinary approach to heart failure that aims to improve a patient’s functional capacity, reduce the risk of hospitalization, and improve long-term survival. Cardiac rehabilitation integrates structured exercise training, lifestyle modifications, and psychosocial support, customized to meet each individual’s needs. Studies demonstrate that exercise capacity, muscle strength, and respiratory efficiency are enhanced with aerobic exercise, resistance training, and inspiratory muscle training. Despite the proven efficacy, there is a significant underutilization of cardiac rehabilitation due to limited availability, low awareness, and patient adherence to the programs. This review article synthesizes evidence from PubMed, Scopus, and reference lists of relevant studies published up to July 2025 highlights the necessity of integrating CR into standard heart failure management and focusing on individualized rehabilitation programs. Enhancing the availability of CR programs could significantly alleviate the burden of HF, improve outcomes, and reduce healthcare expenses associated with frequent hospitalizations. Future research should prioritize a multidisciplinary team approach and patient education to align evidence-based recommendations with practical application.